A new multienzyme-type biosensor for triglyceride determination. Issue 1 (2nd January 2016) - Yücel, Alp; Özcan, Hakkı Mevlüt; Sağıroğlu, Ayten
ABSTRACT: An amperometric multienzyme biosensor for determination of triglycerides (TGs) was constructed by mounting three gelatin membrane-bound enzymes on a glassy carbon electrode (working electrode), then connecting it to electrometer along with an Ag/AgCl reference electrode and a Pt auxiliary electrode. Characterization and optimization of the multienzyme biosensor, which is prepared with glycerol kinase (GK) (E.C.2.7.1.30), glycerol-3-phosphate oxidase (GPO) (EC 1.1.3.21), and lipase (EC 3.1.1.3), were studied. In the optimization studies for the bioactive layer components of the prepared biosensor, the optimum amounts of gelatin, bovine serum albumin (BSA), and glutaraldehyde was calculated as 1 mg/cm 2, 1 mg/cm 2, and 2.5%, respectively. Optimum pH and temperature of the reaction of biosensor were determined as 7.0 and 40°C, respectively. Linear range of triolein for the biosensor was found from the calibration curve between several substrate concentration and Δ Current. After optimization and characterization of the biosensor, its operationability in triglycerides was also tested.